Pemikiran Dr. Nashih Ulwan tentang Pendidikan Akhlak pada Anak Usia Dini - Lase, Rafni Murdani; Hanafiah, Muhammad Ali; Hairunnisa, Hairunnisa (AUD Cendekia: Journal of Islamic Early Childhood Education, 2025)
This study aims to examine Dr. Abdullah Nashih Ulwan’s thoughts on moral education for early childhood and its relevance in the context of modern education. Using a qualitative method with a literature study approach, this research explores Ulwan’s main work Tarbiyatul Aulad fi al-Islam along with supporting literature to uncover the concepts, values, and methods of moral education he proposed. The findings show that Ulwan places moral education at the core of the entire process of child development, based on three main principles: exemplary conduct (uswah), habituation (ta‘wīd), and good advice (maw‘izhah hasanah). The key moral values emphasized include morals toward Allah, oneself, parents and teachers, other people, and the environment. Ulwan’s ideas prove highly relevant in addressing children’s moral challenges in the digital era, as they emphasize the balance between faith, morality, and social behavior. The application of his thought can be implemented in both family settings and early childhood education institutions through the habituation of Islamic values, digital role modeling, and moral supervision. This study offers a synthesis between classical Islamic thought and modern educational theory, resulting in an integrative, spiritual, and contextual model of moral education for early childhood that responds to the challenges of globalization and technological advancement.